Peer Pastoral Accompaniment in Special Needs Education: A Theology of Vulnerability Perspective - Lilis Suryani Sihombing; Sartika Dewi Simanjuntak; Ellyda Destiar Emelia Tambun; Samsudin Sembiring (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Abstract: Disability in educational and pastoral practices is often perceived through a deficit paradigm, positioning persons with disabilities as objects of pastoral care and recipients of assistance. This article aims to challenge such perception by employing the theology of vulnerability as a conceptual foundation for developing an inclusive Christian Religious Education approach within Special Education Schools. This study employs a qualitative method with a systematic literature review approach by critically examining relevant works on pastoral theology, disability theology, and inclusive education. The findings reveal that students with disabilities are not merely individuals who require support but also active subjects capable of participating in and contributing to supportive relationships. This article proposes a peer pastoral accompaniment model as an inclusive Christian Religious Education approach based on three fundamental principles: mutuality, solidarity, and participation. The study concludes that true inclusion emerges when vulnerability becomes a space of shared humanity, not a reason for exclusion.